Evidence for an intramacrophage growth phase of Mycobacterium ulcerans - Torrado, Egídio (2007)
Mycobacterium ulcerans is the etiologic agent of Buruli ulcer (BU), an emerging tropical skin disease. Virulent M. ulcerans secretes mycolactone, a cytotoxic exotoxin with a key pathogenic role. M. ulcerans in biopsy specimens has been described as an extracellular bacillus. In vitro assays have suggested a mycolactone-induced inhibition of M. ulcerans uptake by macrophages in which its proliferation has not been demonstrated. Therefore, and uniquely for a mycobacterium, M. ulcerans has been classified as an extracellular pathogen. In specimens from patients and in mouse footpad lesions, extracellular bacilli were concentrated in central necrotic acellular areas; however, we found bacilli within macrophages in surrounding inflammatory infiltrates. We demonstrated that mycolactone-producing M. ulcerans isolates are efficiently phagocytosed by murine macrophages, indicating that the extracellular location of M. ulcerans is not a result of inhibition of phagocytosis. Additionally, we found that M. ulcerans multiplies inside cultured mouse macrophages when low multiplicities of infection are used to prevent early mycolactone-associated cytotoxicity. Following the proliferation phase within macrophages, M. ulcerans induces the lysis of the infected host cells, becoming extracellular. Our data show that M. ulcerans, like M. tuberculosis, is an intracellular parasite with phases of intramacrophage and extracellular multiplication. The occurrence of an intramacrophage phase is in accordance with the development of cell-mediated and delayed-type hypersensitivity responses in BU patients.